O Processo De Ensino E Aprendizagem Em Ambientes Virtuais: A Constituição Do Ethos Discursivo No Gênero Fórum - Alves, Valeria Espanha [UNIFESP] (2017)
This dissertation inserts itself in the postulates of Discourse Analysis of French line, and of Applied Linguistics and aims to analyze the studies of the language about the ethos and the constitution of the discursive ethos of the subjects involved in the situation of teaching and learning in Distance Education, in the genre forum discussion. It presents as a guiding principle to defend the idea that, in this digital genre, there is an interaction between the subject enunciators that implies the construction of knowledge and the constitution of discursive ethos by coercions characteristic of the academic discourse and the genre. For the construction of the discursive ethos, the subject enunciator can use of individual enunciative strategies that influence or not the belonging of the subject to a particular community of discourse. Our initial hypothesis is that, by means of stereotypes, the discursive ethos of the enunciative subject submitted to the scenography of digital pedagogical shows in a first time, the academic, the literate, subordinate to the norms, autonomous and researcher - of the students – and, dynamic, flexible, expert, manager, and mediator - the teacher. To do so, we selected 20 posts made between a teacher and 13 students. The criterion of choice considered the collective interactions that joining six or more posts in a same group, aiming to collaborative action. The theoretical basis for this research was based mainly on the studies of Maingueneau (1997, 2008, 2010, 2013 e 2015) regarding the discourse, in Silva (2014) regarding collaborative learning and in Moore e Kearsley (2007) to treat the new technologies and discursive forum genre. For analysis, we invested in the following categories: discursive ethos, scenes of enunciation, global semantics and the linguistic traces of person and non-person of the speech. The results demonstrate that the presence of the teacher is essential to mediate the construction of knowledge, since the students themselves do not keep the discourse with a focus on the topic of discourse; the most it stands, leaves to fulfill the activity on the last day of term, without regard to the performative character of the process from intra to inter-learning, when you do not support your argument, being a discursive ethos distanced from contestation. From these results, we conclude that these students still do not have the cultural maturity to act in this modality of education, do not see the genre forum as a space of discussion for placements, and to expand their knowledge, from the analysis, it was verified that their